Solomon Islands : Requests for Purchase under the Rapid Financing Instrument and Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Solomon Islands. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper presents Solomon Island's Requests for Purchase Under the Rapid Financing Instrument and Disbursement Under the Rapid Credit Facility. In order to address the pandemic, the Solomon Islands' authorities have taken measures to prevent the entry of coronavirus disease 2019 (COVID-19), to increase health and containment spending, and to provide targeted support for vulnerable households and businesses. IMF financing will help fill immediate financing needs and catalyze additional financing from its development partners to support the COVID-19 response. The authorities' immediate policy response has focused on strong and timely containment measures to limit the risk of a local outbreak while reprioritizing spending toward health care. They have also adopted a fiscal stimulus package with measures targeted at providing social assistance, protecting jobs and incomes and stabilizing the domestic economy. Beyond the immediate response to the external shock, the authorities should remain committed to policies that promote inclusive growth and resilience while containing external pressures, protecting financial stability and preserving fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet